Known glioma risk loci are associated with glioma with a family history of brain tumours—A case–control gene association study1. Issue 10 (21st November 2012) - Melin, Beatrice; Dahlin, Anna M.; Andersson, Ulrika; Wang, Zhaoming; Henriksson, Roger; Hallmans, Göran; Bondy, Melissa L.; Johansen, Christoffer; Feychting, Maria; Ahlbom, Anders; Kitahara, Cari M.; Wang, Sophia S.; et al.
Abstract Familial cancer can be used to leverage genetic association studies. Recent genome‐wide association studies have reported independent associations between seven single nucleotide polymorphisms (SNPs) and risk of glioma. The aim of this study was to investigate whether glioma cases with a positive family history of brain tumours, defined as having at least one first‐ or second‐degree relative with a history of brain tumour, are associated with known glioma risk loci. One thousand four hundred and thirty‐one glioma cases and 2, 868 cancer‐free controls were identified from four case–control studies and two prospective cohorts from USA, Sweden and Denmark and genotyped for seven SNPs previously reported to be associated with glioma risk in case–control designed studies. Odds ratios were calculated by unconditional logistic regression. In analyses including glioma cases with a family history of brain tumours (n = 104) and control subjects free of glioma at baseline, three of seven SNPs were associated with glioma risk: rs2736100 (5p15.33, TERT), rs4977756 (9p21.3, CDKN2A‐CDKN2B) and rs6010620 (20q13.33, RTEL1). After Bonferroni correction for multiple comparisons, only one marker was statistically significantly associated with glioma risk, rs6010620 (ORtrend for the minor (A) allele, 0.39; 95% CI: 0.25–0.61; Bonferroni adjusted ptrend, 1.7 × 10−4). In conclusion, as previously shown for glioma regardless of family history of brain tumours, rs6010620 (RTEL1) was associated with an increased risk of glioma when restricting to cases with family history of brain tumours. These findings require confirmation in further studies with a larger number of glioma cases with a family history of brain tumours.